VALIDITY OF SUPPLEMENTARY TEACHING MATERIALS ON BUFFER SOLUTION TO TRAIN ARGUMENTATION SKILLS - Noviyana, Dyah Kirani; Suyono, Suyono (JURNAL SPEKTRA, 2024)
The purpose of this research is to produce supplementary teaching materials on buffer solution materials that are valid in practicing argumentation skills. This research is a type of development research that focuses on developing products for learning using the ADDIE model which is limited to the development stage. The instrument used in this research is a validation sheet consisting of content and construct validity. The target of the research is supplementary teaching materials in practicing argumentation skills on buffer solutions. The teaching materials were assessed by 3 validators, namely experts in chemistry learning. The results of the assessment through this validation sheet obtained a mode of 4 which was declared valid. Based on this assessment, it can be concluded that the supplementary teaching materials on buffer solution material are valid in supporting argumentation skills training.